2012
DOI: 10.1002/jmri.23583
|View full text |Cite
|
Sign up to set email alerts
|

Blood oxygenation level‐dependent (BOLD) MRI of human skeletal muscle at 1.5 and 3 T

Abstract: Purpose: To evaluate the dependence of skeletal muscle blood oxygenation level-dependent (BOLD) effect and time course characteristics on magnetic field strength in healthy volunteers using an ischemia/reactive hyperemia paradigm.Materials and Methods: Two consecutive skeletal muscle BOLD magnetic resonance imaging (MRI) measurements in eight healthy volunteers were performed on 1.5 T and 3.0 T whole-body MRI scanners. For both measurements a fat-saturated multi-shot multiecho gradient-echo EPI sequence was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…Differences between MRI and computed tomography (CT) that are advantageous in certain applications include MRI’s better soft tissue contrast, lack of ionizing radiation, and the ability to perform functional and multi-parametric imaging [2]. Clinical validation of the first PET/MRI systems are currently underway [3] and preliminary case series have recently been published including whole-body oncologic imaging [4, 5] and intracranial tumors [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Differences between MRI and computed tomography (CT) that are advantageous in certain applications include MRI’s better soft tissue contrast, lack of ionizing radiation, and the ability to perform functional and multi-parametric imaging [2]. Clinical validation of the first PET/MRI systems are currently underway [3] and preliminary case series have recently been published including whole-body oncologic imaging [4, 5] and intracranial tumors [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…32 However, a recent study using a 3-tesla system showed improved inter-session CVs for BOLD variables, 20 which was presumably attributable to the increased signal-tonoise ratio and BOLD SI contrast with the higher field strength. 22 Our study has several limitations. First, there were few subjects.…”
Section: Discussionmentioning
confidence: 91%
“…14,16,17,22 We applied a conventional sphygmomanometer air cuff for the thigh (86 © 21 cm; Welch Allyn Japan, Tokyo, Japan) to the middle of the left thigh (Fig. 1a) (40-s rest phase), compressed the cuff by applying pressure of 50 mm Hg above the individual's brachial systolic blood pressure to induce ischemia (300-s ischemic phase), and then rapidly reduced compression by opening the air valve, provoking reactive hyperemia (360-s hyperemic phase) (Fig.…”
Section: Cuff-compression Paradigm For Reactive Hyperemiamentioning
confidence: 99%
See 1 more Smart Citation
“…BOLD MR imaging has also been used to evaluate several extra neural organs, including the heart, kidney, liver, uterus, and skeletal muscle [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. For example, BOLD MR imaging of skeletal muscle has been used to evaluate exercise-induced physiological changes in skeletal muscle [7][8][9] and to assess severity of peripheral arterial occlusive disease [12,13].…”
Section: Introductionmentioning
confidence: 99%